Volatile Secondary Metabolites of Hypericum Tetrapterum and Hypericum Bithynicum - Seyis, Fatih; Yurteri, Emine; Ozcan, Aysel; Cirak, Cuneyt; Yayla, Fatih (Pergamon-Elsevier Science Ltd, 2022)
The phytochemical analyses on the flowering aerial parts resulted in identification of 32 and 30 compounds which represent 100% of total volatile components in Hypericum tetrapterum and Hypericum bithynicum (Hypericaceae), respectively. Among the chemicals, methylpalmitate, p-menthone, linalool and alpha-santalene for H. tetrapterum and camphor, alpha-bisabolol, methylpalmitate and nerolidol for H. bithynicum were recognized as major volatile ingredients. Volatile profile of H. tetrapterum from Turkish origin had never been described and this is the first report on volatile chemistry of H. bithynicum. Chemotaxonomic significance of the tested com-pounds was also discussed.
Yurteri, Emine/0000-0002-3770-2714; Özcan Aykutlu, Aysel/0009-0001-0401-2071;
Keywords: Chemical Variability; Chemotaxonomy; Hypericum; Multivariate Analyses; Volatile Components